Relationship between oil price fluctuations and stock price index in Iran - (:unkn) unknown (LLC CPC Business Perspectives, 2015)
The present study aims to investigate the impact of oil price fluctuations and a set of other macroeconomic variables on stock price index using structural vector auto regression models, impulse response function, and variance decomposition during 2001-2013. The results of the study reveal that there is no consensus on the effect of oil price on stock price index in different countries. In other words, a group of studies reported a positive relationship between oil price and stock price index, while other studies have argued that there is no relationship between these variables. © Mahdi Salehi, Mahmoud Lari Dashtbayaz, Mostafa Bahrami, Hossein Mosallapour, 2015.
Keywords: Iran; Oil price; Stock price